2007
DOI: 10.1007/s00268-005-0585-9
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Breast Cancer in Asian Women

Abstract: The inadequacies of health care infrastructures and standards, sociocultural barriers, economic realities, illiteracy, and the differences in the clinical and pathological attributes of this disease in Asian women compared with the rest of the world together result in a different spectrum of the disease. Better socioeconomic conditions, health awareness, and availability of breast cancer screening in developed Asian countries seem to be the major causes of a favorable clinical picture and outcomes in these cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
299
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(326 citation statements)
references
References 25 publications
(28 reference statements)
15
299
1
Order By: Relevance
“…The majority of our cases (33.18%) had 41-50 years. This 10 years earlier peak incidence age for Iranian women is different from developed countries (Parkin and Fernandez, 2006;Smigal et al, 2006) but resembles to developing nations (Agarwal et al, 2007) and corresponds with other studies done in Iran (Mousavi et al, 2007;2008;Harirchi et al, 2011). Some biomarker studies and clinical data point that lateonset BC is biologically less aggressive with a slower growth than early-onset (Fisher et al, 1997;Benz, 2008).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The majority of our cases (33.18%) had 41-50 years. This 10 years earlier peak incidence age for Iranian women is different from developed countries (Parkin and Fernandez, 2006;Smigal et al, 2006) but resembles to developing nations (Agarwal et al, 2007) and corresponds with other studies done in Iran (Mousavi et al, 2007;2008;Harirchi et al, 2011). Some biomarker studies and clinical data point that lateonset BC is biologically less aggressive with a slower growth than early-onset (Fisher et al, 1997;Benz, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…BC is the top cancer in women worldwide and is increasing specially in developing countries, where most of cases are diagnosed in late stages (Agarwal et al, 2007;Mousavi et al, 2008), a finding that is indicated in the current study, as well. Rate of increasing BC in developing countries is reported as 3-4% (Parkin et al, 2001).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…With rising incidence and awareness, breast cancer is the commonest cancer in urban Indian females (Takiar and Vijay, 2010) and the second commonest in the rural Indian women (HBCR, 2001). Over 100,000 new breast cancer patients are estimated to be diagnosed annually in India (Nandakumar et al, 1995;Agarwal et al, 2007). With a rising trend in incidence reported from various registries of National Cancer Registry Programme, presently India has become a country with the largest estimated number of breast cancer deaths worldwide (PBCR, 2001, Nandakumar et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…However, data from Asian countries suggest the rate to be much higher, approaching 10% to 25% (Chopra et al, 2001;Tan et al, 2005;Yip et al, 2006;Lim et al, 2007). In addition, Asian patients present with larger metastatic tumours and often involve multiple metastatic sites (Agarwal et al, 2007). The median survival of de novo metastatic breast cancer (MBC) is unknown as most reported studies included patients who developed metastatic disease after initial treatment for early breast cancer.…”
Section: Introductionmentioning
confidence: 99%